Poszukiwanie innowacyjnych rozwiązań w edukacji przedszkolnej. Doświadczenia nauczycielek pracujących na podstawie programu wychowania przedszkolnego Tablit - Basińska, Anna (Studia Edukacyjne, 2018)
The article presents Tablit – a kindergarten curriculum, its constructivist assumptions as well as innovative methodology: the Project Approach, Questioning the Author and CLIL. Selected experiences of teachers who had tested the curriculum were analyzed.